2011
DOI: 10.1063/1.3622769
|View full text |Cite
|
Sign up to set email alerts
|

Electrical power dissipation in semiconducting carbon nanotubes on single crystal quartz and amorphous SiO2

Abstract: Articles you may be interested inEffect of van der Waals forces on thermal conductance at the interface of a single-wall carbon nanotube array and silicon AIP Advances 4, 127118 (2014); 10.1063/1.4904099Laser irradiation of carbon nanotube films: Effects and heat dissipation probed by Raman spectroscopy

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…27,35 The temperature profile is shown to be dependent on the length as well as on the type of NTs. 26,29,36,37 The temperature is maximum at the middle of short metallic NTs and therefore, the breakdown is expected at the midpoint as shown in Fig. 6(a).…”
Section: Fig 4 (A) I-t and (B) T-t Curves At 18 V (C) I-t And (D)mentioning
confidence: 99%
See 1 more Smart Citation
“…27,35 The temperature profile is shown to be dependent on the length as well as on the type of NTs. 26,29,36,37 The temperature is maximum at the middle of short metallic NTs and therefore, the breakdown is expected at the midpoint as shown in Fig. 6(a).…”
Section: Fig 4 (A) I-t and (B) T-t Curves At 18 V (C) I-t And (D)mentioning
confidence: 99%
“…6(b) and the breakdown is highly probable in this maximum temperature region. 36,37 However, the maximum temperature region shifts toward the middle as the tube diameter increases and the breakdown was expected accordingly [ Fig. 6(b)].…”
Section: Fig 4 (A) I-t and (B) T-t Curves At 18 V (C) I-t And (D)mentioning
confidence: 99%
“…Besides, their surfaces are usually cooled only through natural convection which can make selfheating critical especially for CN-TFTs operating in highfrequency range (~]VIHz) [8,9]. Although CNTs have high thermal conductivity [10,11], the interfacial thermal conductance at CNT-substrate interfaces [12][13][14][15][16][17][18][19] and CNT-CNT junctions [20][21][22][23][24] are very low which can exacerbate the self-heating effects and can significantly degrade the TFT performance.…”
Section: Introductionmentioning
confidence: 99%
“…3,10 Recently, it has been shown that the temperature profile of short semiconducting NT is anisotropic and the breakdown can occur away from the middle. 11,12 However, there is no evidence on the exact position of the breakdown. For technological applications, it is desirable to understand the breakdown position and its predictability.…”
Section: Introductionmentioning
confidence: 99%